Do your ears pop in space? : and 500 mind-bending questions about space travel - Mullane, R. Mike. (New York : Wiley, 1997)
Provides the answers to 500 of the most frequently asked questions about space travel and the astronaut experience, compiled by the author during his post-astronaut career as a public speaker.
Includes index.
Book Links (A.L.A.).
Adult
Keywords: Astronautics -- Miscellanea; Astronautics -- Miscellanea